Effect of Sodium Bicarbonate and Glycogen Depletion on 1500n1 Time Trials - Behr, Laura (My University, 2002)
Previous studies have demonstrated the importance of anaerobic capacity to performance during high intensity exercise. Competitive cyclists/skaters (N = 9) performed three randomly ordered control (C), sodium bicarbonate (SB), glycogen depletion (GD) 1500m cycling time trials. Power output was recorded using a strain gauge interfaced with a windload simulator attached to a racing bicycle. VO2 was measured by open circuit spirometry. Power output and V02 were linked based on steady state exercise completed before the trials. Repeated measures ANOVA analyzed the outcomes. The GD trial took significantly longer than the C or SB trials ((333.96, SB133.49, & GD137.73~p) < .05. Mean total and anaerobic power output during the last 200m segment was significantly greater in SB compared to GD (C42879, SB44956 & GD40642 J), and (C20189, SB22194 & GD18741 J), but not for aerobic work (C22683, SB22762 & GD21901 J). The results support the hypothesis of augmenting anaerobic capacity during the sodium bicarbonate trial and reducing anaerobic capacity with glycogen depletion.
Keywords: Cycling - Physiological aspects; Glycogen - Metabolism; Sodium bicarbonate - Physiological effect